Stigma and Discriminations Suffered by Mental Patients and their Caregivers in the Ho Municipality of Ghana - Tawiah, P.E. (University of Ghana, 2012)
Stigma and discrimination is becoming a global issue that permeates many communicable diseases. Stigma creates a barrier between the sick and the rest of society that prevents them from acting on their instinctive desire to seek curative treatment that will enable them to reenter into their everyday social activity. This study was done in Ho Municipality of Ghana. It explored the forms of stigmatization and discrimination against mental disorders, social meaning and the coping strategies adopted by mentally ill and their care givers. The study adopted mixed method using structured questionnaire and semi-structured interview guide. Two hundred and seventy seven mentally disordered patients were purposively interviewed. Four Focus Group Discussion were held for caregivers and five mental health professionals were interviewed as key informants. The quantitative data were analysed using SPSS and Excel whilst the interviews were coded and analysed thematically. The study generally revealed that Mental disorder appears to cut across all categories of human background; age, gender, education, ethnicity, employment, marital status. More females were stigmatized than males at the work/employment and educational levels. The forms of stigma and discrimination noted at the patient level were of social stigma (including hiding from public, verbal abuse, family blame, ridiculing and mockery of family members and colleague patients looking mean upon the individual) and psychological stigma (i.e. loss of self-esteem) and economic (i.e. no food). Social forms of discrimination associated with mental disorders include loss of friends, spousal desertion, exclusion from family and withdrawal or refusal of admission into schools. Others include refusal of the community members to marry from their families, and denial and delay of access to medical treatment. Economical discriminations suffered include loss of financial support, no access to clothing, loss of accommodation and no food. Caregivers also were stigmatized and discriminated as due to their specialty. The coping strategies adopted by the mental patients and their caregivers against stigma and discrimination include aggression, hope in God, Prayers and hoping condition will change one day. In conclusion, stigma is a social sickness attached mental disorders thereby making the disease burden heavier.
Thesis (MSc) - University of Ghana, 2012